Interatrial Septum Assessment by Transthoracic Echocardiography Part 1: Secundum ASD - Alicia Rangosch; Valeria E. Duarte; Miguel A. Quiñones (Methodist DeBakey Cardiovascular Journal)
This 10-minute video aims at improving skills for the structural assessment of the interatrial septum using 2-dimensional transthoracic echocardiography (TTE) to increase the ability to diagnose—or rule out—the different types of interatrial communications. Of the five types of lesions, this video focuses on ostium secundum atrial septal defect. This is the first video in our MicroLearning Video Series, designed to help a target audience of sonographers, general cardiologists, general practitioners who want to gain knowledge on fundamental cardiology, and technicians. View the video at https://vimeo.com/989145537/4898c3c590.